'#OccupyGezi Architecture' and Archival Tactics of Resistance. (1st July 2020) - Artan, Elif Çiğdem
AbstractHerkes için Mimarlık ('Architecture for All', HiM) is a group of architects, urban planners, designers, and sociologists who conduct participatory renovation projects. They were involved in the Occupy Gezi Park movement by questioning top-down urban politics in Istanbul, developing a series of online and on-site events including the Gezi Festivals, interview videos, timelines, zines, and exhibitions. Working from these case studies, this article examines the ways HiM archived the occupied milieu as a means of resistance: How do the materials that HiM documented during the Occupy Gezi Park movement contribute to knowledge production through a non-authoritarian and a non-linear history writing? I argue that temporality plays a crucial role in this process, as it is impossible to predetermine the duration of a protest movement and the course of events complicates decision-making regarding what to include or exclude in the archive. Through in-depth interviews and archival research that focus on HiM's public events and design works, this article examines the group's curatorial and documentation practices with respect to questions of authenticity, authorship, accessibility, and security.